Impartial Law Enforcement By The Indonesian Criminal Justice System In The Civil Law System - Sari, Nani Widya; Ekawati, Dian; Prayitno, Isnu Harjo; Munalar, Sri Siti; Purgito, Purgito (Faculty of Law, Andalas University, 2024)
This writing aims to understand law enforcement by the existing criminal justice system and to understand the existing legal system models in the world and Indonesia along with their characteristics. The method used in this writing is normative legal research through literature study with data collection methods in the form of secondary data. The results of the research show that law enforcement has not been implemented optimally, so it is very important that the existing criminal justice system can work well to create and realize a sense of justice in society. In this world, there are two models of the rule of law concept that have been developed, namely the Continental European model called rechstaat and the Anglo Saxon model called the rule of law. The concept of rechtsstaat was born from a struggle against absolutism so that it is revolutionary in nature. The concept of rechtsstaat relies on the Continental Law system called civil law. Meanwhile, the concept of the rule of law develops evolutionarily, which is based on a legal system called common law.